2015
DOI: 10.1097/nmd.0000000000000296
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behavior and Mortality in First-Episode Psychosis

Abstract: Suicide is a serious public health problem, with more than 800,000 deaths taking place worldwide each year. Mental disorders are associated with increased risk of suicide. In schizophrenia and other psychotic disorders, the lifetime risk of suicide death is estimated to be 5.6%. The risk is particularly high during the first year of the initial contact with mental health services, being almost twice as high as in the later course of the illness. The most consistently reported risk factor for suicide among peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
89
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 51 publications
12
89
1
3
Order By: Relevance
“…Serious mental health conditions and suicide after loss of a close relative are potentially preventable. Early mitigation of risk may have wide‐ranging beneficial effects, especially for distinct high‐risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…Serious mental health conditions and suicide after loss of a close relative are potentially preventable. Early mitigation of risk may have wide‐ranging beneficial effects, especially for distinct high‐risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for suicide in patients with first-episode schizophrenia (FES) are reported as longer duration of untreated psychosis (DUP), severe or variable depressive symptoms, using antipsychotic drugs, higher levels of feelings of guilt, and anxiety (Barrett et al, 2010(Barrett et al, , 2015Melle and Ann Barrett, 2012;Palmier-Claus et al, 2013;Upthegrove et al, 2014), conviction of a violent crime, and having a first-degree relative with a schizophrenia/bipolar diagnosis (Björkenstam et al, 2014), young age, female sex, and history of suicide attempt (Nordentoft et al, 2015). Melle and Ann Barret (2012) also reported that risk of suicide attempt before first admission was associated with the length of untreated illness.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of attempted suicide in psychotic patients ranged from 10 to 50% (Melle et al, 2006, Power and McGowan, 2011). Up to 40–79% of individuals affected with Schizophrenia report suicidal ideation at least once during the course of illness (Fenton et al, 1997, Skodlar et al, 2008), where the estimated suicide rate is 579/100,000 person years and the lifetime risk of suicidal death is 5.6% (Hor and Taylor, 2010, Nordentoft et al, 2015). …”
Section: Introductionmentioning
confidence: 99%